If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 2(c + 1) + 2 Reorder the terms: 10 = 2(1 + c) + 2 10 = (1 * 2 + c * 2) + 2 10 = (2 + 2c) + 2 Reorder the terms: 10 = 2 + 2 + 2c Combine like terms: 2 + 2 = 4 10 = 4 + 2c Solving 10 = 4 + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. 10 + -2c = 4 + 2c + -2c Combine like terms: 2c + -2c = 0 10 + -2c = 4 + 0 10 + -2c = 4 Add '-10' to each side of the equation. 10 + -10 + -2c = 4 + -10 Combine like terms: 10 + -10 = 0 0 + -2c = 4 + -10 -2c = 4 + -10 Combine like terms: 4 + -10 = -6 -2c = -6 Divide each side by '-2'. c = 3 Simplifying c = 3
| 7(3x-2)=5(2x-1) | | 24x-3(8x-18)=54 | | 6x+2(2x-3)=24 | | 7p-6p=-11 | | Y=0.25x^2+10x+80 | | 3x^(-1/2)=8 | | 12-v=9 | | 4x+5x-34=68-8x | | 3x^(-1/2)-8=0 | | (a*a)-5a+25+(b*b)+6b+36=0 | | -6=3(x-19) | | 4x+x-15+x-4=180 | | 6-2x=6x-10x-16 | | 5b+6b-9b+1=7 | | 2(1-2a)=7(a-6) | | 2(x-3)-3=3 | | 11=4(n-17)+15 | | 7-z=-3 | | 12x+24y=60 | | ((4y^4/3x^4y^7))^3 | | 4s-3s=15 | | 8a^4=9a^2 | | 1/2:1/2 | | (a*a)-5a+25+(b*b)+6b+61=0 | | 11x+-9x-3=-9 | | G(x)=f(x+3)+1 | | (4y^4/3x^4y^7)^3 | | 11x+-9r-3=-9 | | c+x^2+40x=0 | | 13+x=y-17 | | -20x+5y=15 | | -5(r+7)=88 |